Principles of Security and Trust 7th International Conference, POST 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Bauer, Lujo; Küsters, Ralf (Security and Cryptology,, 2018)
This book is Open Access under a CC BY licence.